The transducible TAT-RIZ1-PR protein exerts histone methyltransferase activity and tumor-suppressive functions in human malignant meningiomas. (July 2015) - Ding, Mao-Hua; Wang, Zhen; Jiang, Lei; Fu, Hua-Lin; Gao, Jie; Lin, Xian-Bin; Zhang, Chun-Lei; Liu, Zhen-Yang; Shi, Yi-Fei; Qiu, Guan-Zhong; Ma, Yue; Cui, Da-Xiang; et al.
Abstract: Malignant meningiomas are a rare meningioma subtype and tend to have post-surgical recurrence. Significant endeavors have been taken to identify functional therapeutic targets to halt the growth of this aggressive cancer. We have recently discovered that RIZ1 is downregulated in high-grade meningiomas, and RIZ1 overexpression inhibits proliferation while promoting cell apoptosis of the IOMM-Lee malignant meningioma cell line. In this report, we show that the N-terminal PR domain of RIZ1 alone possessed growth-inhibitory activity and anticancer activity in primary human meningioma cells. Interestingly, the effects seem to be dependent on differential RIZ1 protein levels. Transducible TAT-RIZ1-PR protein could also inhibit meningioma tumor growth in nude mice models. We further demonstrate that PR protein exerts histone methyltransferase activity. A microarray analysis of TAT-RIZ1-PR-treated human malignant meningioma cells reveals 969 differentially expressed genes and 848 alternative splicing exons. Moreover, c-Myc and TXNIP, two putative downstream targets of H3K9 methylation, may be involved in regulating RIZ1 tumor-suppressive effects. The reciprocal relationship between RIZ1 and c-Myc was then validated in primary meningioma cells and human tumor samples. These findings provide insights into RIZ1 tumor suppression mechanisms and suggest that TAT-RIZ1-PR protein is a potential new epigenetic therapeutic agent for advanced meningiomas.